Economic management in Ireland post-EMU: policy implications of globalisation and regionalisation - Bradley, John (Statistical and Social Inquiry Society of Ireland, 1999)
In today?s increasingly globalised economy, it is something of a paradox that while policy-making autonomy is being progressively ceded by states to supranational organisations, regions within nation states have also begun to assert their rights to a greater degree of administrative and policy self-determination. However, just as the exercise of certain types of policy autonomy in the past for small states like Ireland was not always without problems, policy integration of regions into nation states ? such as Scotland and Northern Ireland ? has not necessarily provided them with guaranteed participation in the prosperity of other richer regions within their nation state.
Symposium on economic management in Ireland post-EMU
Read before the Society, 18 February 1999
Keywords: Economic management; Economic policy; Globalisation; Irish economic growth; 314.15